Beszélgetések a pszichoanalízisről 3/5 Pszcihoanalízis és emberkép
Perhaps it was not accidental that Freud's first significant and at the same time most original work "The Interpretation of Dreams" was published at the dawn of the 20th century. This book, as the standard work of the new science, laid down analysis of dreams to be the "royal road" to the unconscious, to still unknown psychic areas of man. Poets and philosophers had already known a lot about the secrets of the mind, but Freud was the first to grasp it in its entirety in "The Interpretation of Dreams". Here he wrote for the first time that dreams, just like psychic illnesses, were the results of the struggle between conscious and unconscious psychic forces. The method of free association elaborated in the course of treatment made the art of listening to be the tool of healing again. The Freudian concept of man, just like Musil's novels and Schönberg's music, reflects the crisis of the Austro-Hungarian Empire and the critical stage of liberalism of that time. According to the world concept of liberalism man is independent, free and rational in his thoughts, intentions and decisions. But Freud thought that a considerable part of psychic life happens unconsciously, and that man is not a "master of his own house". He is able to obtain knowledge of his genuine, inner drives by analyzing them carefully. At the beginning psychoanalysis met resistance just like Kepler's and Darwin's scientific discoveries, as it called attention to the significance of infantile sexuality, that later became a stumbling block. Freud also threw light on the complexity of parent-child relationships and he called it the Oedipal Complex, after the ancient Greek drama. It was not easy to make all these acceptable in the contemporary, hypocritical Vienna, although Freud emphasized the controlling role of society and culture over the strength of instincts. In these conversations, we trace these ideas. Péter Forgács